EXCURSIONS IN MODERN EDUCATION IN UKRAINE - Narovlyanskiy, Oleksandr (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article is devoted to developing educational tourism at the present stage of Ukrainian education. The purpose of the article is to determine the current state of development of educational tourism in Ukraine and the problems that exist in educational excursions. Following the goal, the tasks were solved: to analyze information about the number of educational excursions held in educational institutions of Ukraine; to determine the level of involvement of students in educational excursions and students’ attitude to educational excursions; to determine shortcomings in the conduct of excursions, the influence of the content of educational programs on how to use excursions in the educational process of studying certain educational subjects. The analysis of information on the development of tourism and local history work in the regions of Ukraine, obtained by the Ukrainian State Center for National and Patriotic Education, Local History and Tourism of Student Youth, regulations, current curricula for grades 1-11, as well as the results of a survey of Ukrainian school students, was used. The regulations of the Cabinet of Ministers of Ukraine and the Ministry of Education and Science of Ukraine that influence the development of educational excursions are identified. The information on excursions conducted in Ukraine’s secondary and out-of-school educational institutions (2018-2023) is analyzed. Development dynamics are determined, and assumptions are made about the reasons for the decrease in the number of excursions during this period. The article analyzes the results of a survey of Ukrainian students on educational excursions conducted in 2024, in which 671 students in grades 1-11 from 10 regions of Ukraine took part. It was found that some educational institutions do not conduct excursions at all. The author analyzes the distribution of excursions by objects of inspection, their types and duration, and the subjects on which excursions are conducted. It was found that the methodological level of many excursions needed to be increased. Teachers need to pay more attention to preparing for excursions, use more assignments for students on the excursion, and, in many cases, the excursion material is not used in other educational activities. The analysis of current curricula for grades 1-11, including the New Ukrainian School model curricula for grades 1-7, was conducted. It was determined that many programs must provide study tours and pay attention to their educational potential. Programs in a number of subjects, including history, also prefer virtual excursions, ignoring the possibilities of real excursions, in particular in the course of Ukrainian history.